1998
DOI: 10.5326/15473317-34-4-325
|View full text |Cite
|
Sign up to set email alerts
|

Morbidity and mortality associated with anesthetic management in small animal veterinary practice in Ontario

Abstract: During 1993, 66 small animal practices participated in a prospective study to evaluate the incidence and details of anesthetic-related morbidity and mortality. Considering a total of 8,087 dogs and 8,702 cats undergoing anesthesia, the incidences of complications were 2.1% and 1.3%, respectively. Death occurred in 0.11% and 0.1% of cases, respectively. Logistic regression models were developed and showed that a significant odds ratio (OR) of complications in dogs was associated with xylazine (OR, 91.5); heart … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
168
2
19

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 166 publications
(226 citation statements)
references
References 9 publications
6
168
2
19
Order By: Relevance
“…A xilazina estimula os receptores alfa-2 pós-sinápticos, produzindo vasoconstrição de curto período de ação (MUIR & MASON, 1993), e, posteriormente, a pressão arterial Tabela 2 -Protocolos anestésicos utilizados em cães e gatos que vieram a óbito, correlacionados ao índice percentual de mortalidade em relação ao número total de óbitos de cada espécie. DYSON et al (1998), demonstra que existe uma taxa de probabilidade de 91,5% de complicações transoperatórias em cães associadas ao uso de xilazina. Ainda nesse mesmo estudo, observou-se que a xilazina esteve envolvida em 43,6% das paradas cardíacas em cães.…”
Section: Resultsunclassified
“…A xilazina estimula os receptores alfa-2 pós-sinápticos, produzindo vasoconstrição de curto período de ação (MUIR & MASON, 1993), e, posteriormente, a pressão arterial Tabela 2 -Protocolos anestésicos utilizados em cães e gatos que vieram a óbito, correlacionados ao índice percentual de mortalidade em relação ao número total de óbitos de cada espécie. DYSON et al (1998), demonstra que existe uma taxa de probabilidade de 91,5% de complicações transoperatórias em cães associadas ao uso de xilazina. Ainda nesse mesmo estudo, observou-se que a xilazina esteve envolvida em 43,6% das paradas cardíacas em cães.…”
Section: Resultsunclassified
“…Pferdeheilkunde 26 519 her than the rate described in companion animals (0.11% (Dyson et al 1998 (Lagasse et al 2002)). …”
Section: S Picek Et Almentioning
confidence: 95%
“…Xylazine itself has been implicated in several anaesthetic-related adverse issues. Twenty-five percent of complications in one study involved the use of xylazine in the veterinary anaesthetic protocol (Dyson et al, 1998). And an increased anaesthetic related mortality rate was observed in cats and dogs given xylazine (Clarke and Hall, 1990).…”
Section: Ketamine-xylazine Is Still the Most Commonly Used Injectablementioning
confidence: 99%
“…In veterinary practice, one study reported a 1 in 679 mortality rate in dogs and cats undergoing anaesthesia and another study recorded 48 in 3546 mortality due to anaesthetic related complications equating to approximately 1.4% (Whelan and Flecknell, 1992, Clarke and Hall, 1990, Bille et al, 2012. Mortality rates as low as 1 in 10,000 was recorded in the medical field (Dyson et al, 1998). In comparison, the Researchers' attitude towards acceptable losses varies from 1.4% as unacceptable to 9% being considered low (Whelan and Flecknell, 1992).…”
Section: Anaesthetic Related Mortality Rates In Laboratory Rodents Armentioning
confidence: 99%